Symptom Stability in Rome IV vs Rome III Irritable Bowel Syndrome - Barberio, Brigida; Houghton, Lesley A.; Yiannakou, Yan; Savarino, Edoardo V.; Black, Christopher J.; Ford, Alexander C. (The American journal of gastroenterology, 2021)
Irritable bowel syndrome (IBS) is a chronic functional bowel disorder, which follows a relapsing and remitting course. Little is known about how evolving definitions of IBS or treatment for the condition affect symptom stability. We conducted a 12-month longitudinal follow-up study of individuals who self-identified as having IBS to examine these issues. We collected demographic, gastrointestinal symptom, mood, and psychological health data at baseline, and gastrointestinal symptom data at 12 months, from adults who self-identified as having IBS, registered with 3 organizations providing services to people with IBS. We applied the Rome III and Rome IV criteria simultaneously at baseline and 12 months and subtyped participants according to predominant stool form or frequency. We examined stability of a diagnosis of IBS, and stability of IBS subtype, for the Rome IV and III criteria separately and examined the effect of commencing new therapy on fluctuation of symptoms. Of 1,375 individuals recruited at baseline, 784 (57.0%) provided data at 12 months. Of these, 452 met the Rome IV criteria for IBS at baseline, of whom 133 (29.4%) fluctuated to another functional bowel disorder at 12 months. In the remaining 319 (70.6%) who still met the Rome IV criteria for IBS, IBS subtype changed in 101 (31.7%) subjects, with IBS with mixed bowel habit (IBS-M) the least stable. Commencing a new treatment for IBS did not affect symptom stability. Among 631 who met the Rome III criteria at baseline responding at 12 months, 104 (16.5%) fluctuated to another functional bowel disorder. In the 527 (83.5%) who still met the Rome III criteria for IBS, IBS subtype fluctuated in 129 (24.5%), with IBS-M the most stable subtype. Again, commencing a new treatment for IBS did not affect symptom stability. Fluctuation between functional bowel disorders and predominant stool subtype is common in people with IBS and does not appear to be influenced solely by treatment. Rome IV IBS appears less stable than Rome III IBS.